Characterisation and partition of valuable metals from WEEE in weathered municipal solid waste incineration bottom ash, with a view to recovering. (1st May 2019) - Pérez-Martínez, S.; Giro-Paloma, J.; Maldonado-Alameda, A.; Formosa, J.; Queralt, I.; Chimenos, J.M.
Abstract: As the demand for critical and valuable metals increases due to industrial developments, especially in electronics and high-technology industries, the search for novel and sustainable sources grows in significance. Incinerated municipal solid waste (MSW) is a potential source of valuable metals, since a lot of waste from electrical and electronic equipment (WEEE) is not recycled properly and are is managed together with the refuse fraction of MSW, which is often landfilled or incinerated. Bottom Ash (BA) is the main by-product of incinerated MSW, which has been characterized to assess the potential recovery of valuable metals. The determination of the total amount of valuable metals (Ag, Al, Au, Be, Co, Cu, Ga, Ge, In, Ir, Li, Ni, Pd, Pt, Sb, Ta, and W) in seasonal samples of weather bottom ash (WBA) was performed by a total acid digestion followed by a chemical analysis. Besides, a sequential extraction procedure (SEP) is conducted to define their partition. The characterisation has shown that the content of valuable metals in the incineration WBA, which was highest in the 0–2 mm fraction was much lower than in concentrated ores commonly used as primary sources. Moreover, the SEP showed little potential for the valorisation of most of the metals, as they are embedded in or bound to a silicic matrix or sintered metal oxides, and so their extraction requires strong-acid digestion or a highly oxidizing environment. This work contributes to the use of residual sources as secondary resources and to the correct management of the end-of-life electrical and electronic equipment. Highlights: WEEE are not recycled properly and are managed with the refuse fraction of MSW. MSWI bottom ash is a potential source of valuable metals coming from WEEE. MSWI bottom ash has been characterized to evaluate the recovery of valuable metals. Valuable metals are mainly in fine fractions with lower contents than mineral sources. Valuable metals are embedded in Si-matrix and require severe condition for extraction.